The optic radiations and reading development: A longitudinal study of children born term and preterm - Lisa Bruckert; Garikoitz Lerma-Usabiaga; Lauren R. Borchers; Virginia A. Marchman; Katherine E. Travis; Heidi M. Feldman (Developmental Cognitive Neuroscience)
Purpose: To determine if reading development between ages 6 and 8 years related to changes in fractional anisotropy (FA) in the optic radiations (OR), and if these associations were similar in children born full term (FT) and preterm (PT) and in language tracts. Methods: FT (n = 34) and PT (n = 34) children completed the Word Identification subtest of the Woodcock Reading Mastery Test at 6, 7, and 8 years. Diffusion MRI (96-directions, b=2500 sec/mm2) was acquired at 6 and 8 years. Probabilistic tractography identified bilateral OR and three left-hemisphere language tracts: inferior longitudinal fasciculus (ILF), superior longitudinal fasciculus (SLF), and arcuate fasciculus (AF). Linear mixed models determined if FA changes in these tracts were associated with reading growth. Results: Rates of reading growth were similar in both groups. For the OR, FA change from 6 to 8 years was negatively associated with reading growth in both groups. A similar pattern was observed in the left ILF but not in the SLF or AF. Conclusion: Individual differences in reading development were associated with FA change of the OR and left ILF in FT and PT children. Negative associations implicate increasing axonal diameter and/or complexity in fiber structure as drivers of faster reading development.